KOMUNIKASI MORAL RELIGIUS MELALUI DONGENG PADA SELAPARANG TV - Alf, Ahmad Hamdian (Universitas Islam Negeri Mataram, 2018)
This paper uses a case study approach, in addition to obtaining valid data, the author here collects data with structured interview techniques, full participant observation and documentation analysis. Communication is used by storytellers in conveying moral messages through the Selaparang TV media namely verbal and nonverbal communication. Verbal communication is used when narrating or telling fairy tales, while nonverbal communication is used in the form of illustrations from fairy tales brought. The communication process that occurs in the feld is secondary communication where storytellers convey moral messages through television media. The moral message conveyed is more about the stories of prophet Muhammad SAW.